PEMAHAMAN MAHASISWA TENTANG KOMUNIKASI TRADISIONAL - Chusmeru Chusmeru (Jurusan Ilmu Komunkasi FISIP Universitas Jenderal Soedirman, 2017)
The development of modern mass media has shifted the traditional communication media presencein the area. People are more interested in watching the spectacle on television and in social mediathan watch traditional arts. The method used a descriptive method with qualitative researchapproaches. Data collection methods used interviews, observation, and documentation. Researchcarried out on college students participating in the Traditional Communications. Results showedthat although the media has shifted the traditional communication media presence, but thestudents are still able to understand the kinds of traditional communication in the region, they canexplain the function and meaning of the message contained in the traditional arts in the region